New Insights into LINC00346 and its Role in Disease - Lu, Juan; Xiao, Zhaoying; Xu, Mengqiu; Li, Lanjuan (Frontiers in Cell and Developmental Biology, 2022)
Accumulating evidence has shown that long intergenic non-protein-coding RNA 346 (LINC00346) functions as an oncogene in the tumorigenesis of several cancers. The expression level of LINC00346 has been shown to be obviously correlated with prognosis, lymphoma metastasis, histological grade, TNM stage, tumor size and pathologic stage. LINC00346 has been found to regulate specific cellular functions by interacting with several molecules and signaling pathways. In this review, we summarize recent evidence concerning the role of LINC00346 in the occurrence and development of diseases. We also discuss the potential clinical utility of LINC00346, thereby providing new insight into the diagnosis and treatment of diseases. In addition, we further discuss the potential clinical utility of LINC00346 in the diagnosis, prognostication, and treatment of diseases.